Permeação de gases através de membrana composta por grafeno epoli(dimetilsiloxano) - Mariana Ogando Paraense (2017)
The preparation of monolayer and bilayer graphene composite membranes supported by poly(dimethylsiloxane) (PDMS) as well as the analysis of the transfer and characterization of materials was carried out in this work. The synthesis of graphene by chemical vapor deposition (CVD) enabled the growth of high quality samples. The transfer of monolayer graphene from the copper substrate to PDMS did not significantly change its structure and there was no generation of extra defects. The wet transfer method with poly(methylmethacrylate) (PMMA) is more effective in producing membranes with barrier properties, overlapping by 30% the properties of the membranes without PMMA. In Raman spectroscopy, it was observed D, G and 2D bands near theircommon values for graphene. Raman maps indicated that the transfer of graphene was performed in the whole area of the samples. Atomic-force microscopy (AFM) revealed that the monolayer and bilayer of graphene supported by PDMS is not flat, and that a wave pattern, with valleys and hills, appears in the 3D image of the surface. In gas permeation tests, the composite membranes of graphene and PDMS were distant of the Robeson upper bound for the pair CO2=N2. The selectivity of the pair CO2=N2 was constant and near 6.5 for all samples. The layers of graphene over PDMS were capable of reducing the permeability of the gases CO2 e N2 in 32%, revealing their potential as a gas barrier device for gas separation applications.